Challenges Facing Women Cooperatives in Accessing Markets for Agricultural Products: A Systematic Literature Review - Msosa, Steven Kayambazinthu (International Review of Management and Marketing, 2022)
Co-operatives enable women who would have been isolated and working alone to band together and produce economies of scale whilst also increasing their negotiating power in the market. However, despite the quest to access the markets as a unit, women cooperatives face several challenges that hinder their progress. This study sought to analyse the challenges facing women cooperatives in accessing markets for agricultural products. A systematic literature review was conducted using several academic databases. Thus, a plethora of studies on women cooperatives published between 2011 and 2022 were reviewed. The findings of this study show that women cooperatives’ access to markets is hampered by a lack of information about markets, transportation problems, structural and cultural constraints, and a lack of skills. This study is expected to contribute to the extant literature on women cooperatives and could assist scholars, policy-makers and practitioners to understand the dynamics of the challenges affecting women cooperatives. Such an understanding could help in reviewing and re-designing policies aimed at opening up markets for women cooperatives.